"Do I exist in this world, really, or is it just her?" Youths' perspectives of living with a sibling with anorexia nervosa. Issue 1 (2nd January 2020) - Fjermestad, K. W; Rø, A. E.; Espeland, K. E.; Halvorsen, M.S.; Halvorsen, I. M.
ABSTRACT: Little is known about how severe anorexia nervosa (AN) in youths affects siblings and siblings' experiences of family-based treatment for AN. Thirteen youths ( M age = 15.5 years, SD  = 3.0; 23% boys) who had been co-admitted with their sibling with AN and parents at an inpatient clinic for eating disorders 3 to 6 years earlier participated in qualitative interviews. Interviews were analyzed using systematic text condensation. Results showed AN is difficult to understand, particularly at onset, and is associated with confusion and lack of information for siblings. AN evokes difficult emotions, including fears of death, frustration about rigid behavior, and sadness about changed life situations. AN affects family dynamics and relations, including conflicts and disruptions at home, limited and divided family life, and less attention from parents and extended family. Siblings pay attention to other people eating habits, strive for a balanced view on eating, and experience family meals as conflictual. Siblings experience increased knowledge and personal development, and are ambivalent to family treatment. Ways of coping include creating distance, seeking social support, rationalizing, and keeping hope. In conclusion, siblings' experiences of severe AN are complex and ambiguous. Family-based treatment for AN in young people should address siblings' perspectives.